A Quantitative Synthesis of Eight Decades of Global Multiple Sclerosis Research Using Bibliometrics - Ismail, Ismail Ibrahim; Saqr, Mohammed (Frontiers in Neurology, 2022)
Bibliometric studies on the field of multiple sclerosis (MS) research are scarce in the literature. The aim of this study is to offer an overarching view of the body of knowledge about MS research over eight decades from 1945–2021 by means of a bibliometric analysis. We performed a quantitative analysis of a massive dataset based on Web of Science. The analysis included frequencies, temporal trends, collaboration networks, clusters of research themes, and an in-depth qualitative analysis. A total of 48,356 articles, with 1,766,086 citations were retrieved. Global MS research showed a steady increase with an annual growth rate of 6.4 %, with more than half of the scientific production published in the last decade. Published articles came from 98 different countries by 123,569 authors in 3, 267 journals, with the United States ranking first in number of publications (12,770) and citations (610,334). A co-occurrence network analysis formed four main themes of research covering the pathophysiological mechanisms, neuropsychological symptoms, diagnostic modalities, and treatment of MS. A noticeable increase in research on cognition, depression, and fatigue was observed, highlighting the increased attention to quality of life of patients with MS. This bibliometrics analysis provided a comprehensive overview of the status of global MS research over the past eight decades. These results could provide a better understanding of this field, and help identifying new directions for future research.